PERSEPSI MASYARAKAT DAERAH PENYANGGA TERHADAP FUNGSI EKOLOGI TAMAN NASIONAL BUKIT BARISAN SELATAN - Firnanda, Edo; Harianto, Sugeng P.; Winarno, Gunardi Djoko; Wulandari, Christine; Dewi, Bainah Sari; Fitriana, Yulia Rahm (Lambung Mangkurat University-Indonesia, 2024)
Perception significantly influences an individual's behavior towards their environment. An accurate understanding of forest conservation typically leads to a positive attitude toward environmental protection efforts. This relationship suggests that perception shapes attitudes and behaviors, encouraging active participation in forest conservation and ecological protection. In Margomulyo Village, a buffer village of Bukit Barisan Selatan National Park (BBSNP), community perceptions play a critical role in conservation efforts. Understanding these perceptions is vital for assessing awareness of forest sustainability, which is essential for maintaining ecosystem balance. This study aimed to: 1) Evaluate the level of community perception, and 2) Explore the relationship between social characteristics and community perceptions of the ecological function of the BBSNP forest. Research was conducted in Margomulyo Village, Semaka District, Tanggamus Regency, from March to April 2020. Data were collected through direct observation and interviews with 60 respondents selected by purposive sampling, with random sampling applied for respondent selection. Spearman Rank correlation analysis was used to investigate the relationship between social characteristics and perceptions. Results indicated generally high community perceptions of the forest’s ecological function, with environmental aspects rated at 3.8, economic aspects at 3.7, and socio-cultural aspects at 3.5 on the Likert scale. Significant positive correlations were found with age (correlation value of 0.465, significance value of 0.007) and formal education level (correlation value of 0.816, significance value of 0.005).